Using aword-space model to determine the relevance of messages in anchored asynchronous online discussions - Raga, Rodolfo C. (Animo Repository, 2008)
This paper presents results of the first phase of our study aimed at investigating the applicability of word-space models, particularly those generated using Random Indexing (RI) technique, for the task of determining the relevance of messages posted in anchored asynchronous online discussion forums. In this phase, we addressed several questions intended to establish baseline figures: How efficient will the word-space model perform in this task? How much of its classification decisions align with the decisions of the human annotators? More importantly, does the paradigmatic and syntagmatic contexts of words have a direct effect on its output and which produces the best results? Using Cohen's Kappa and Holsti's Coefficient Reliability measure, our experiments generated an initial reliability performance (K=0.41, CR=0.72). It further indicated that the syntagmatic context is more applicable for this task. We concluded with a discussion of the weaknesses identified and possible means of improving the level of performance. © 2008 by Rodolfo Raga, Jennifer Raga, Eric Bonus, and Raymund Sison.